XRCC5 VNTR, XRCC6 -61C>G, and XRCC7 6721G>T Gene Polymorphisms Associated with Male Infertility Risk: Evidences from Case-Control and In Silico Studies - Danial Jahantigh; Abasalt Hosseinzadeh Colagar (International Journal of Endocrinology)
We evaluate the association between genetic polymorphisms of XRCC5 VNTR, XRCC6 -61C>G, and XRCC7 6721G>T with male infertility susceptibility. A total of 392 men including 178 infertile males (102 idiopathic azoospermia and 76 severe oligozoospermia) and 214 healthy controls were recruited. XRCC6 -61C>G and XRCC7 6721G>T genotyping was performed by PCR-RFLP whereas XRCC5 VNTR was performed by PCR. The 2R allele and 2R allele carriers of XRCC5 VNTR polymorphism significantly decreased risk of male infertility. The mutant GG genotypes and carriers of the CG and GG genotypes of XRCC6 -61C>G showed increased risk for the male infertility. Furthermore, the G allele of the XRCC6 -61C>G was correlated with increased susceptibility to male infertility. Likewise, the T allele of the XRCC7 6721G>T polymorphism was associated with increased susceptibility to male infertility in azoospermia. In silico analysis predicted that the presence of tandem repeats in XRCC5 gene prompter can be sequence to bind to more nuclear factors. Also, rs2267437 (C>G) variant was located in a well-conserved region in XRCC6 promoter and this variation might lead to differential allelic expression. The XRCC7 6721G>T gene polymorphism occurred in an acceptor-splicing site, but this polymorphism has no severe modification on XRCC7 mRNA splicing. Our results indicate the association of XRCC5 VNTR, XRCC6 -61C>G, and XRCC7 6721G>T gene polymorphisms with male infertility in Iranian men.